How to organise and operate a small business in Australia - English, John. (St Leonards, NSW : Allen and Unwin, 1998)
This is a complete handbook of samll business management. Every chapter has been thoroughly revised to present information, skills and approaches that are easy to understand and simple to use.
Keywords: Management; Small business; Small business -- Management; Small business -- Australia -- Management